2018
DOI: 10.18203/2349-3291.ijcp20183369
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum IgE levels in childhood asthma in Barabanki region, India

Abstract: Background: Elevated Serum Immunoglobulin E (IgE) levels are characteristic of most of the allergic diseases including asthma. Most of the asthma patients are allergic to inhaled antigens and chemical antigens, which lead to their sensitization and induce a state of hypersensitivity that is IgE mediated hypersensitivity reaction. The aim of this study was to estimate and compare serum IgE levels in childhood asthmatics and in normal subjects and to obtain the relationship between serum IgE levels and severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The majority (n=56, 80%) cases showed IgE level >150IU/ml, and the mean total IgE was 800.9 ± 883.2IU/ml. This is similar to the study by Rathoria et al who reported the mean IgE levels in childhood asthma to be 881.81IU/ml [13]. This is consistent with previous reports suggesting serum IgE be characteristics of most allergic diseases including asthma [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…The majority (n=56, 80%) cases showed IgE level >150IU/ml, and the mean total IgE was 800.9 ± 883.2IU/ml. This is similar to the study by Rathoria et al who reported the mean IgE levels in childhood asthma to be 881.81IU/ml [13]. This is consistent with previous reports suggesting serum IgE be characteristics of most allergic diseases including asthma [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…It has been noted that the mean serum tIgE levels in children with asthma was significantly higher than those in normal controls (p value <0.001). [16][17][18][19] In this study serum tIgE levels were above the normal limit for age in 86.2% patients with asthma. Chandran et al, Chaudhary et al, and Lama et al, found raised serum tIgE levels in 75% ,71.4% and 63.3% of asthmatic children respectively.…”
Section: Discussionmentioning
confidence: 87%
“…903,906,[908][909][910][911][912] Mean value of total IgE based on Indian Studies is varies from 65-128 IU/mL in non-atopic population and 269-1136 IU/m L in atopic population. 845,867,[912][913][914][915][916][917] Majority of Indian studies are hospital-based compared to studies conducted overseas. The Euro-Prevall INCO study on prevalence of food sensitization and probable food allergy among adults in India 923 reported that the mean value of total IgE was 529IU/L.…”
Section: Q 15 What Are Indications For Intradermal Testing In Respira...mentioning
confidence: 99%